{5,10-dihydro-silanthrene as a reagent for the Barton-McCombie reaction} - Gimisis, T.; Ballestri, M.; Ferreri, C; Chatgilialoglu, C; Boukherroub, R.; Manuel, G. (Tetrahedron Lett., 1995)
The deoxygenation of secondary alcohols via thionoesters with the use of 5,10-dihydrosilanthrene as the radical reducing agent has been studied in detail. The ability of hydrogen donation of this silane has been measured using the one-carbon ring expansion of 1-(2-oxocyclopentyl)ethyl radical as a timing device.